POTRET PENDIDIKAN AGAMA ISLAM DI LINGKUNGAN MULTIKULTURAL SEKOLAH INDONESIA DI MALAYSIA - Tri Prasetiyo, Nova (JPG: Jurnal Pendidikan Guru, 2025)
This study aims to describe the learning practices of Islamic Religious Education (PAI) in the multicultural environment of Sekolah Indonesia Kota Kinabalu and Community Learning Center (CLC) Malaysia. This research used qualitative method. Data collection techniques were conducted through observation, in-depth interviews with teachers. The results showed that the dominance of cognitive aspects has led to an imbalance between the mastery of religious material and students' moral practices. As a result, some students show exclusive, intolerant, and less empathic attitudes in daily interactions. The findings emphasize the need for a more holistic reconstruction of the PAI model, by integrating cognitive, affective, and psychomotor domains and integrating local and multicultural contexts. PAI teachers should act more as facilitators and create collaborative spaces, facilitate moral simulations, and connect materials with real life so that learning not only produces intellectual intelligence, but also inclusive, tolerant characters, and is able to implement Islamic values. Researchers suggest that learning includes affective and psychomotor indicators explicitly based on religious moderation, the provision of interactive media and contextual modules, and teacher training in character-based learning strategies and religious moderation.